UI/UX Optimization for OTP (One-Time Password) Verification in Digital Health Apps using Design Thinking - Muhamad Raihan Alghazali; Ghamar Hafidz; Ucu Nugraha (Jurnal Sistem Informasi dan Teknologi Informasi, 2025)
The rapid advancement of digital technology in the healthcare sector has catalyzed the development of applications such as XYZ, which offer streamlined access to medical services. However, security remains a critical challenge, particularly regarding the One-Time Password (OTP) authentication process. Issues such as delayed code delivery, insufficient system feedback, and ambiguous user guidance frequently degrade the overall user experience. This study aims to enhance the usability and effectiveness of the OTP verification process within the XYZ application using the Design Thinking methodology. The methodology comprises five distinct phases: Empathize, Define, Ideate, Prototype, and Test. Findings from the Empathize and Define stages identified core pain points from the user’s perspective. The Ideate phase generated innovative solutions, including multi-channel OTP resend options, destination number validation, and informative system feedback with integrated help features. High-fidelity prototypes were developed using Figma and evaluated through internal usability testing to measure ease of use and operational effectiveness. The results demonstrate that the Design Thinking approach produces solutions more closely aligned with user needs, significantly improving the quality and reliability of the OTP verification process.